Trauma, Ethics and the Political Beyond PTSD The Dislocations of the Real - Bistoen, G. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
The contemporary psychiatric approach to trauma, encapsulated in the diagnostic category of PTSD, has been criticized for its neglect of the political dimensions involved in the etiology and treatment of trauma. By means of a philosophical and psychoanalytical analysis, the depoliticizing potential of the biomedical approach is tied to a more general 'ethical crisis' in post-traditional societies. Via the work of Lacan, Žižek and Badiou on the act and the event, this book constructs a conceptual framework that revives the ethical and political dimensions of trauma recovery.